Reinsurance in the Third World - Irukwu, J. O. (Nigeria The Caxton Press, 1986)
This book is a companion to students of reinsurance and practitioners alike.
includes appendixes
ijb, 18/01/2019
Loans
Keywords: Reinsurance; Developing countries